Operational Resilience in Digital Payments : Experiences and Issues - Khiaonarong, Tanai (IMF Working Papers; Working Paper ;, 2021)
Major operational incidents in payment systems suggest the need to improve their resiliency. Meanwhile, as payment infrastructures become more digitalized, integrated, and interdependent, they require an even higher degree of resilience. Moreover, risks that could trigger major disruptions have become more acute given the rise in power outages, cyber incidents, and natural disasters. International experiences suggest the need to strengthen reliability objectives, redundancies, assessment of critical service providers, endpoint security, and alternative arrangements.